The role of arbuscular mycorrhizal fungi on ecosystem multifunctionality across phenological phases under warming in alpine meadows - Keyu Chen; Xiaoyue Yin; Luming Ding; Jingying Feng; Wubuli Subinuer; Changting Wang; Xinhua He; Chuangming Yang (CATENA, 2026)

Quantifying lamina-controlled variations in rock physical properties from AI-reconstructed 3D multimineral digital rocks - Yuqi Wu; Yumei Ao; Jiabao Yang; Zijie Lu; Keyu Liu; Yuchen Fan; Jianhua Zhao; Li Hou; Bo Liao; Pejman Tahmasebi (International Journal of Rock Mechanics and Mining Sciences, 2026)

UAV-based measurements of methane emissions from two electrically-driven natural gas compressor stations in China - Tianran Han; Wang Tian; Yuheng Zhang; Jietao Zhou; Yanrong Yang; Keyu Chen; Lei Ren; Chuanfeng Wang; Yufei Huang; Haijiong Sun; Xinyi Chen; Chang Liu; et al. (Environmental Pollution, 2026)

Modification of Lycium ruthenicum pomace dietary fibers: Enhanced physicochemical, structural, and functional properties - Huiling Li; Keyu Tian; Ruiqi Wang; Ruyu Shangguan; Jingna Yang; Nana Yang; Xintao Meng; Xiang Li; Ting Zhang; Hongjie Lei (Food Chemistry, 2026)

Spatial heterogeneity of organic carbon in muddy tidal flat sediments - Xiangxiang He; Cai Zhang; Weifang Gu; Keyu Tao; Yuwei Liu; Jiawei Ding; Xufeng Yang; Peisong Yu (Journal of Oceanology and Limnology, 2026)

Quantitative evaluation of sedimentary filling characteristics, patterns and controlling factors on the typical passive continental margin basin, rift basin, and cratonic basin: Insight from 3D stratigraphic forward modeling - Huiling Yang; Weilin Zhu; Keyu Liu (Journal of Asian Earth Sciences, 2026)

Novel inter-cable wire rope dampers for hanger cable vibration control: Experiment, FE modeling method, and Field test - Shilong Yang; Keyu Lai; Wei Fan; Yuling Liu; Zhiheng Chen; Zhengqing Chen (Engineering Structures, 2026)

Temperature-induced metabolic reconfiguration and community shifts reveal the mechanistic basis of cold inhibition on anammox consortia - Rongrong Chang; Jinluo Pang; Keyu Chen; Chaoxi Yang; Yamiao Yang; Baocheng Huang; Rencun Jin (ENGINEERING Environment, 2026)

Diagenetic evolution of clay minerals and impacts on reservoir quality of the Wufeng and Longmaxi Shale in Sichuan Basin of China - Yang Chen; Jianhua Zhao; Qinhong Hu; Keyu Liu; Mengxiang Yu; Wei Wu; Chao Luo (Applied Clay Science, 2026)

Research on the ion-extraction demulsification mechanism and fiber-particle-induced coalescence for deep oil removal from high-salinity gas-field produced water - Haonan Liu; Keyu Wang; Yiqian Liu; Qiang Yang (Water Research, 2026)

Functional repositioning of aerobic granular sludge as a nitrite-producing pretreatment for mainstream Anammox driven by slowly biodegradable organic matter - Zongshuo Han; Xiaoying Zheng; Jiaqing Tao; Yunqing Li; Keyu Chen; Ruijie Hu; Yifan Zhou; Yang Zhang (Process Safety and Environmental Protection, 2026)

A layered classification framework of near-infrared waste plastic identification through interpretable machine learning - Keyu Zhu; Junrong Chen; Ruizhe Tu; Changlin Cao; Weiming Zhou; Songwei Yang; Qingrong Qian; Qinghua Chen; Kunsen Lin (Journal of Environmental Chemical Engineering, 2026)

Combining medium coalescence filtration and combined fiber coalescence: A pilot study on treating washing wastewater from shipboard EGR systems - Yu Li; Jinwei Xue; Guangyao Zhang; Yiqian Liu; Haonan Liu; Keyu Wang; Xin Han; Qiang Yang (Journal of Environmental Chemical Engineering, 2026)

Thermodynamically-driven selective phase reconstruction repairs kinetic of iron oxalate anodes for stable Li/Na storage - Yichong Kong; Binxin Yu; Keyu Zhang; Binbin Li; Bo Jin; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2026)

Maternal effects enhance offspring performance in the marine rotifer Brachionus plicatilis after exposure to BDE-47 and its photodegradation product BDE-28 - Na Lu; Chunchen Liu; Keyu Lu; Zhen Che; Boyuan Wang; You Wang; Yingying Yang (Journal of Oceanology and Limnology, 2026)

RoofX-Net: A tailored approach to accurate multi-type rooftop segmentation in remote sensing images using edge and scale awareness - Keyu Chen; Tianlei Wang; Zhiyou Yang; Fan Li; Ma Luo; Ruoning Zhang; Hong Qu; Wenyu Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Low‑intensity aeration enhances algal–bacterial synergy to improve nitrogen removal from wastewater with low carbon-to-nitrogen ratio - Yunqing Li; Xiaoying Zheng; Ruijie Hu; Jiaqing Tao; Zongshuo Han; Keyu Chen; Yifan Zhou; Yang Zhang; Wei Chen (Bioresource Technology, 2026)

Bacillus Cereus C3 Addition Facilitates Carbohydrate Degradation and Earthworm Growth During Vermicomposting of Sewage Sludge - Tiantian Tian; Xinge Cui; Wenxing He; Keyu Liu; Jiran Zhang; Shimin Zhang; Xitian Yang; Kun Wu; Xianqin Jiao; Shuxia Xu (Water, Air, & Soil Pollution, 2026)

‘1347B’ module confers durable stripe rust resistance in wheat - Hongkui Fu; Delin Li; Huaizhi Zhang; Yongxing Chen; Ping Lu; Miaomiao Li; Gaojie Wang; Keyu Zhu; Lei Dong; Jian Yang; Chunhuan Chen; Bin Bai; et al. (Theoretical and Applied Genetics, 2026)

Mapping biology in space: from spatial transcriptomics platforms to analytical tools and databases - Zi-Zhen Guo; Renyan Wu; Weixiang Li; Keyu Yang; Xuexiang Ying; Hamid Alinejad-Rokny; Youqiong Ye (Science Bulletin, 2026)

Smart optical imaging-assisted acoustic streaming enrichment system for targeted microalgae screening under multiple stress conditions - Yihan Ma; Longfei Chen; Yifan Wang; Tao Jiang; Chen Yang; Xiaotong Si; Yantong Liu; Keyu Chen; Fenghua Jiang; Chengjun Sun; Xuan Xiao; Yi Yang (Bioresource Technology, 2026)

The Role of Coagulation-Related Genes in Glioblastoma: A Comprehensive Analysis of the Tumor Microenvironment, Prognosis, and Treatment - Jingyi Yang; Lei Shen; Yuankun Cai; Ji Wu; Keyu Chen; Dongyuan Xu; Yu Lei; Songshan Chai; Nanxiang Xiong (Biochemical Genetics, 2026)

Guttulatic calcite evidence for carboniferous icehouse climate in the Ordos Basin, North China Craton - Jiaqi Yang; Zhiliang He; Juntao Zhang; Keyu Liu; Macro Brandano; Jingbin Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Marine flooding induced basinal brine mixing and carbonate cementation: An example from Cretaceous ultra-deep clastic reservoirs in the Kuqa Depression, western China - Shunyu Wang; Jian Wang; Keyu Liu; Yong Li; Zhenkun Li; Meiyi Chen; Leilei Yang (Marine and Petroleum Geology, 2025)

Artificial perches improve the stability of soil microbial networks in degraded alpine steppe of Sanjiangyuan National Park - Yanhe Wang; Mingxin Yang; Keyu Chen; Dongzhi Huangqing; Shouxing Wang; Xiaochun Ning; Hongkui Yang; Qiang Gu; Huakun Zhou (Journal of Environmental Management, 2025)

Fiber-regulated vibration suppression and mechanical behavior of CFRP corrugated channel cored sandwich structures - Jiaming Sun; Yanlong Xu; Keyu Zhu; Leilei Yan; Xitao Zheng; Zhichun Yang (Engineering Structures, 2025)

Delayed progression of diabetic cataractogenesis and retinopathy by topical administration of highly biocompatible carbon dots derived from Scutellaria barbata and Herba hedyotis diffusae - Jiawei Wang; Yihan Zhao; Xueying Yang; Can Li; Keyu Liu; Chenzhao Ma; Yanyan Jiang; Jianqiao Li (Chemical Engineering Journal, 2025)

Paleoenvironment and organic matter enrichment in the Kaijiang–Liangping Trough across the Emeishan Large Igneous Province (ELIP) - Mengxiang Yu; Jianhua Zhao; Keyu Liu; Qinhong Hu; Wei Wu; Quanyou Liu; Chao Luo; Yang Chen; Hongyu Ma; Zhijun Jin (Marine and Petroleum Geology, 2025)

Short-term emissions effect of rainfall erosion on soil CO2 in red soil sloped farmland in southern China - Keyu Yan; Xiaohan Mei; Chuan Zhang; Yanmei Hu; Daoxiang Wang; Zhengfa Chen; Xiaofeng Yang; Yanrui Shao; Yanjun Mao (Soil and Tillage Research, 2025)

Transgenerational effects and mechanisms of nano-SiO2 on pulmonary - Jiangliang Chu; Chengzhi Liu; Shuang Chen; Yifan Yang; Keyu Zhang; Yiping Fu; Beilei Yuan; Zhe Wang (Reproductive Toxicology, 2025)

Performance and mechanism of enhanced phosphorus release and volatile fatty acid production from Fe-P sludge via co-fermenting with agricultural wastes - Wei Yao; Rongrong Chang; Keyu Chen; Chaoxi Yang; Yan Lu; Shixu Wang; Kaiyue Dong; Baocheng Huang; Rencun Jin (Journal of Environmental Sciences, 2025)

Enhanced rare-earth doped mechanoluminescent piezoelectric heterojunction semiconductors through interface engineering with tunable photonic responses for advanced sensing applications - Fanlei Qin; Yujie Chen; Qinglong Hu; Keyu Han; Zhen Xiao; Yang Zhang; Gongxun Bai (Chemical Engineering Journal, 2025)

Multi-stage evolution of the Ordos Basin: Its coupled basin-mountain systems and energy resource - Yiwen Ju; Wei Wang; Zhanli Ren; Zhi Yang; Keyu Liu; Bing Hou; Lei Xiao (Science China Earth Sciences, 2025)

A temporal correlation topology graph model based on mode-intrinsic and mode-specific characterization using differentiated decoupling module with distribution independence constraints for multimode adaptive process monitoring - Keyu Yao; Hongbo Shi; Bing Song; Yang Tao (Process Safety and Environmental Protection, 2025)

Activation of the Nrf2 Signaling Pathway by Tetrahydroberberine Suppresses Ferroptosis and Enhances Functional Recovery Following Spinal Cord Injury - Xiang Li; Heng Yu; Rongjie Liu; Jiansen Miao; Junlei Lv; Shu Yang; Yuxuan Zhu; Yan Chen; Keyu Lu; Chongan Huang; Xiangyang Wang (Molecular Neurobiology, 2025)

Impact of Proton Pump Inhibitors on Osimertinib-Induced Cardiotoxicity in NSCLC Patients - Haitao Wang; Sinan Ma; Weijia Huang; Keyu Chen; Jiao Xie; Na Wang; Youjia Li; Qianting Yang; Xin Yang; Yan Wang (Cardiovascular Toxicology, 2025)

Evolution of the Dibei condensate gas reservoirs in the northern Kuqa Foreland Basin, western China: Insight for hydrocarbon in-reservoir alteration - Xinzhuo Wei; Keyu Liu; Xianzhang Yang; Peng Yang; Jianliang Liu; Xiujian Ding (Marine and Petroleum Geology, 2025)

Soil with high plant available water capacity can mitigate the risk of wheat growth under drought conditions in southeastern Australia - Keyu Xiang; Bin Wang; De Li Liu; Chao Chen; Fei Ji; Yanmin Yang; Siyi Li; Mingxia Huang; Alfredo Huete; Qiang Yu (European Journal of Agronomy, 2025)

Integration of transcriptomics and metabolomics reveal cytotoxic mechanisms of Polyethylene terephthalate microplastics in BEAS-2B cells - Jiangliang Chu; Yifan Yang; Keyu Zhang; Yiping Fu; Beilei Yuan (Food and Chemical Toxicology, 2025)

Coupled evolution of basin structure and fluids recorded by microfractures: A case study of deep-buried ordovician in the tarim basin - Jian Wang; Dongping Tan; Yingchang Cao; Jun Han; Haijun Yang; Yin Liu; Keyu Liu (Marine and Petroleum Geology, 2024)

Changes in soil inorganic carbon following vegetation restoration in the cropland on the Loess Plateau in China: A meta-analysis - Zhenyu Zhao; Keyu Ren; Yang Gao; Mengfan Zhao; Long Zhou; Shaofeng Huo; Jiabin Liu (Journal of Environmental Management, 2024)

Crystal and micro-nano structure bidirectional regulation of iron oxalate for high-lithium storage and ultralong-cycling life via ultrasound assistance - Qing Zhao; Keyu Zhang; Geng Gao; Bo Jin; Guangping Zi; Rui Yan; Binbin Li; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Eco-friendly synthesis of silver nanoparticles against mosquitoes: Pesticidal impact and indispensable biosafety assessment - Chunzhi Wang; Yang Jiang; Keyu He; Yán Wāng (Science of The Total Environment, 2024)

Spatial mapping of greenhouse gases using a UAV monitoring platform over a megacity in China - Tianran Han; Conghui Xie; Yanrong Yang; Yuheng Zhang; Yufei Huang; Yayong Liu; Keyu Chen; Haijiong Sun; Jietao Zhou; Chang Liu; Junfei Guo; Zhijun Wu; et al. (Science of The Total Environment, 2024)

Three birds with one stone: Constructing Janus multilayer carbon fabric to boost solar-driven interfacial evaporation, electrical power generation and inhibit VOCs volatilization - Keyu Ding; Yaqin Yang; Yanan Mao; Dongdong Tong; Shizhou Lu; Bo Song (Chemical Engineering Journal, 2024)

Degradation of Bisphenol A by manganese minerals: The impact of inorganic and organic ligands - Huan He; Feiyuan Liu; Zhicheng Liao; Min Shi; Keyu Ma; Shanshan Yang; Bin Huang; Xuejun Pan (Journal of Environmental Chemical Engineering, 2024)

Active prelithiation strategies for advanced lithium storage systems: A perspective from electrochemical mechanism to structural design and application - Bo Jin; Keyu Zhang; Geng Gao; Qing Zhao; Xinyu Jiang; Dingfang Cui; Keqi Chen; Xiang Lin; Liuliu Liu; Rui Yan; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Direct evidence of gas flushing oil in deep reservoirs: Insight from integrated fluid inclusion analyses - Xinzhuo Wei; Keyu Liu; Wenfang Yuan; Peng Yang; Lu Zhou; Jianliang Liu; Haijun Yang; Xiujian Ding (Organic Geochemistry, 2024)

Boosting activity on CoFe layered double hydroxide by doping and heterostructure as a bifunctional electrocatalyst for efficient overall water splitting - Jian Tang; Junxian Hu; Xuanli Chen; Bin Yang; Keyu Zhang; Yin Li; Yaochun Yao; Shaoze Zhang (Fuel, 2024)

A novel magnetic resonance tuning-magnetic relaxation switching sensor based on Gd-MOF/USPIO assembly for sensitive and convenient aflatoxin B1 detection - Shiqin Dai; Keyu Xing; Yanna Jiao; Shaoyi Yu; Xingyu Yang; Li Yao; Pei Jia; Yunhui Cheng; Zhou Xu (Food Chemistry, 2024)

Frond characteristics of Cyrillopteris (ex. Odontopteris) orbicularis (Halle) comb. et emend. nov.: New evidence from the Permian Upper Shihezi (Upper Shihhotse) Formation of North China - Mingli Wan; Dandan Li; Shan Wan; Wan Yang; Weiming Zhou; Keyu Wang; Kaige Jiang; Jun Wang (Review of Palaeobotany and Palynology, 2024)

Four-decades of sediment transport variations in the Yellow River on the Loess Plateau using Landsat imagery - Zhiqiang Qiu; Dong Liu; Mengwei Duan; Panpan Chen; Chen Yang; Keyu Li; Hongtao Duan (Remote Sensing of Environment, 2024)

Fluid tracing and evolution at micron-scale of shales in faulted lake basin: Evidence and constraints from in-situ analysis of analcime - Junran Wang; Chao Liang; Yingchang Cao; Shunyao Song; Keyu Liu; Shengyu Yang; Jinqiang Tian; Danish Khan; Bixiao Xin (Marine and Petroleum Geology, 2024)

Occurrence of ochratoxin A in Sichuan bacon from different geographical regions and characterization and biocontrol of ochratoxigenic Aspergillus westerdijkiae strain 21G2-1A - Kaidi Hu; Keyu Guo; Xingjie Wang; Song Wang; Jianlong Li; Qin Li; Ning Zhao; Aiping Liu; Li He; Xinjie Hu; Yong Yang; Likou Zou; et al. (Food Research International, 2024)

Porous rod-like structured ternary nitride heterocatalyst Co3Mo3N/Ni3Mo3N for efficient and stable hydrogen evolution reaction - Jian Tang; Shaoze Zhang; Yixing Zeng; Bin Yang; Keyu Zhang; Yin Li; Yaochun Yao; Junxian Hu (Chemical Engineering Journal, 2024)

Effects of natural extract from medicinal herbs on broilers experimentally infected with Eimeria tenella - Yuanyuan Jiang; Yujuan Zeng; Keyu Chen; Haoran Cheng; Songjiang Dai; Xuexue Deng; Long Wang; Jinqiu Liao; Ruiwu Yang; Li Zhang (Veterinary Parasitology, 2024)

Integration of hydrothermal liquefied sludge as wastewater for anaerobic treatment and energy recovery: Aqueous phase characterization, anaerobic digestion performance and energy balance analysis - Changhao Liu; Zhengbo Yue; Ding Ma; Keyu Li; Pengcheng Zhao; Manyi Yang; Jin Wang (Journal of Water Process Engineering, 2024)

A stronger association of mental disorders with smaller particulate matter and a modifying effect of air temperature - Keyu Wu; Junwen Tao; Qiyue Wu; Hong Su; Cunrui Huang; Qingrong Xia; Cuizhen Zhu; Jing Wei; Min Yang; Junwei Yan; Jian Cheng (Environmental Pollution, 2024)

Salinization mechanism of lakes and controls on organic matter enrichment: From present to deep-time records - Chao Liang; Bo Yang; Yingchang Cao; Keyu Liu; Jing Wu; Fang Hao; Yu Han; Wanlu Han (Earth-Science Reviews, 2024)

ERS Mediated by GRP-78/PERK/CHOP Signaling Is Involved in Fluoride-Induced Ameloblast Apoptosis - Li Jinyi; Yang Keyu; Dai Shanshan; He Shuyang; Liu Ruirui; Guo Qingyu; Liu Fei (Biological Trace Element Research, 2024)

Investigation on catalytic distillation dehydrogenation of perhydro-benzyltoluene: Reaction kinetics, modeling and process analysis - Qinglian Wang; Keyu Le; Yi Lin; Wang Yin; Yixiong Lin; Maria V. Alekseeva; Vadim A. Yakovlev; Anton P. Koskin; Chen Yang; Ting Qiu (Chemical Engineering Journal, 2024)

Long-term fencing can't benefit plant and microbial network stability of alpine meadow and alpine steppe in Three-River-Source National Park - Keyu Chen; Sen Xing; Hailan Shi; Yu Tang; Mingxin Yang; Qiang Gu; Yaoming Li; Jing Zhang; Baoming Ji (Science of The Total Environment, 2023)

Variations and causes of in-situ stress orientations in the Dibei-Tuziluoke Gas Field in the Kuqa Foreland Basin, western China - Guoding Yu; Keyu Liu; Kelai Xi; Xianzhang Yang; Jing Yuan; Zhenping Xu; Lu Zhou; Shaoyong Hou (Marine and Petroleum Geology, 2023)

Enhancing the sewage treatment effect, reducing membrane fouling, and increasing microbial community diversity by a novel biofiller-carrying functional bacteria Rhodococcus sp. CPZ24 in a moving bed biofilm reactor - Peizhen Chen; Dongkai Chen; Bo Yang; Keyu Zhang; Shaopeng Li (Journal of Water Process Engineering, 2023)

Geochemistry of syntaxial calcite veins in ultra-deep sandstone reservoirs from the Kuqa depression, western China - Shunyu Wang; Keyu Liu; Jian Wang; Yong Li; Zhenkun Li; Haijun Yang; Tao Mo (Journal of Structural Geology, 2023)

Effect of using construction and demolition waste as substrate on methane and carbon dioxide emissions from green roofs - Xinping Li; Yuanmao Lin; Xiaoling Liu; Jie Liang; Xin Yang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Zhaolan Wei; Xiaochan An; Wei Chen; et al. (Ecological Engineering, 2023)

Differential hydrocarbon generation and evolution of typical terrestrial gas-prone source rocks: An example from the Kuqa foreland basin, NW China - Jianliang Liu; Xianzhang Yang; Keyu Liu; Zhenping Xu; Kun Jia; Lu Zhou; Hongxing Wei; Liang Zhang; Shaojun Wu; Xinzhuo Wei (Marine and Petroleum Geology, 2023)

The influence of CO2 partial pressure on the stability of dawsonite-based on water-rock physical experiment and numerical simulation - Fulai Li; Chun Zhang; Kaining Wang; Wenkuan Ma; Jianlei Yang; Qizhen Du; Shaogui Deng; Keyu Liu (Applied Geochemistry, 2023)

A new gymnospermous stem from the Moscovian (Carboniferous) of North China, and its palaeoecological significance for the Cathaysian Flora at the early evolutionary stage - Keyu Wang; Xing Huang; Wan Yang; Jun Wang; Mingli Wan (Review of Palaeobotany and Palynology, 2023)

Performance of wire rope damper in vibration reduction of stay cable - Keyu Lai; Wei Fan; Zhengqing Chen; Chao Yang; Zhiwen Liu; Shouying Li (Engineering Structures, 2023)

Creating aligned porous structure with cobweb-like cellulose nanofibrils in MXene composite aerogel for solar-thermal desalination and humidity response - Mingqi Ding; Wenjie Ma; Pengju Liu; Jingbo Yang; Keyu Lan; Dawei Xu (Chemical Engineering Journal, 2023)

A systematic review and meta-analysis of air pollution and angina pectoris attacks: identification of hazardous pollutant, short-term effect, and vulnerable population - Min Yang; Keyu Wu; Qiyue Wu; Cunrui Huang; Zhiwei Xu; Hung Chak Ho; Junwen Tao; Hao Zheng; Mohammad Zahid Hossain; Wenyi Zhang; Ning Wang; Hong Su; et al. (Environmental Science and Pollution Research, 2023)

Abnormal ambient temperature change increases the risk of out-of-hospital cardiac arrest: A systematic review and meta-analysis of exposure types, risk, and vulnerable populations - Qiyue Wu; Min Yang; Keyu Wu; Hong Su; Cunrui Huang; Zhiwei Xu; Hung Chak Ho; Hao Zheng; Wenyi Zhang; Junwen Tao; Thi Anh Thu Dang; Mohammad Zahid Hossain; et al. (Science of The Total Environment, 2023)

Preface: Petroleum Geology of the Ordos Basin - Jinhua Fu; Keyu Liu; Jingchun Tian; Renchao Yang; Tian Yang (Journal of Asian Earth Sciences, 2023)

Towards Realizing Intelligent Coordinated Controllers for Multi-USV Systems Using Abstract Training Environments - Sulemana Nantogma; Keyu Pan; Weilong Song; Renwei Luo; Yang Xu (Journal of Marine Science and Engineering, 2021)
Unmanned autonomous vehicles for various civilian and military applications have become a particularly interesting research area. Despite their many potential applications, a related technological challenge is realizing realistic coordinated autonomous control and decision making in complex and multi-agent environments. Machine learning approaches have been largely employed in simplified simulations to acquire intelligent control systems in multi-agent settings. However, the complexity of the physical environment, unrealistic assumptions, and lack of abstract physical environments derail the process of transition from simulation to real systems. This work presents a modular framework for automated data acquisition, training, and the evaluation of multiple unmanned surface vehicles controllers that facilitate prior knowledge integration and human-guided learning in a closed-loop. To realize this, we first present a digital maritime environment of multiple unmanned surface vehicles that abstracts the real-world dynamics in our application domain. Then, a behavior-driven artificial immune-inspired fuzzy classifier systems approach that is capable of optimizing agents’ behaviors and action selection in a multi-agent environment is presented. Evaluation scenarios of different combat missions are presented to demonstrate the performance of the system. Simulation results show that the resulting controllers can achieved an average wining rate between 52% and 98% in all test cases, indicating the effectiveness of the proposed approach and its feasibility in realizing adaptive controllers for efficient multiple unmanned systems’ cooperative decision making. We believe that this system can facilitate the simulation, data acquisition, training, and evaluation of practical cooperative unmanned vehicles’ controllers in a closed-loop.

Construction of a small-caliber tissue-engineered blood vessel using icariin-loaded β-cyclodextrin sulfate for in situ anticoagulation and endothelialization - Jingyuan Yang; Keyu Wei; Yeqin Wang; Yanzhao Li; Ning Ding; Da Huo; Tianran Wang; Guanyuan Yang; Mingcan Yang; Tan Ju; Weng Zeng; Chuhong Zhu (Science China Life Sciences, 2018)

Identification of long non-coding RNA p34822 as a potential plasma biomarker for the diagnosis of hepatocellular carcinoma - Cheng Wang; Tianyu Ren; Keyu Wang; Shaogeng Zhang; Shubin Liu; Hu Chen; Penghui Yang (Science China Life Sciences, 2017)

Taking climate, land use, and social economy into estimation of carbon budget in the Guanzhong-Tianshui Economic Region of China - Ting Li; Jing Li; Zixiang Zhou; Yanze Wang; Xiaonan Yang; Keyu Qin; Jingya Liu (Environmental Science and Pollution Research, 2017)

Production of marker-free transgenic rice expressing tissue-specific Bt gene - Chengxiang Qiu; Jatinder Singh Sangha; Fengshun Song; Zhiyun Zhou; Ao Yin; Keyu Gu; Dongsheng Tian; Jianbo Yang; Zhongchao Yin (Plant Cell Reports, 2010)